Magnetorheological suspension control using Matlab and Arduino PID controller for the Formula Malaysia Education Competition (Formula MEC) - Ismail, Mohamad Amiruddin Bin; Nashir, Irdayanti binti Mat; Sethuprakash, V.; Sekiguchi, Kazuma; Soyoung, Lee (CENTRAL ASIA AND THE CAUCASUS, 2022)
Formula MEC car development using a magnetorheological (MR) suspension system has become popular and necessary nowadays. There are less studies in this field. Some of literature review was done to gain basic information and knowledge of the FMEC formula car in designing a multiple degree-of-freedom mass-spring damper, the mathematical model involved, and the controller using Matlab/Simulink. The next step was to determine the parameters of the formula car, such as mass and damper spring resistance. Based on the mathematical model, the system was designed in Simulink using the force disturbance obtained from previous experiments. After successfully simulating the system, the controller was designed using Simulink and tested. The test results obtained from the MR damper were compared to determine the parameters that yielded the best performance towards reducing vehicle vibrations. A prototype of the MR damper was built in Simulink and Arduino microcontroller, which was a major contribution of this research. The MR Damper was designed according to the Formula MEC specifications. A quarter car system for the formula car was designed following the equations of a 2DOF system. In the next phase, a simulation was conducted to aid in the design of the MR Formula MEC damper.